A policy analysis of procurement practices among grocery retailers in Zimbabwe - Mlambo, Sephath; Njerekai, C. (Midlands State University, 2015)
This study was undertaken with the aim of exposing the policies and practices of grocery retailers in Zimbabwe. The research was prompted by the paucity of data on grocery retailing in the country and yet this sector is one of the key economic activities in the country today. Since procurement is the nerve centre of all retail activities, this exploratory study was undertaken in a bid to generate insight and issues for further research in this area. A multiple case study approach was adopted for the study in which ten (10) major retailers in terms of turnover and employment were taken as the study units. Researcher administered questionnaires aimed at the chief or principal buyers of the chosen retailers were the primary data collection instruments. Secondary data in the form of company documents were also used to augment the primary data collection techniques employed by the researchers. This study revealed that there was a yawning absence of clear cut buying policies and procedures among grocery retailers in Zimbabwe. In relation to buying practices, this paper revealed that, retail buying was largely a decentralised activity. The study also revealed that, although there were a number of buying issues and concerns affecting the retailers buying practices in Zimbabwe, their practices largely reflected international theory and practice. The paper therefore recommends that all the issues and retail buying challenges raised in this paper be subjected to further research in order to provide a richer data base for the retailing sector in the country. In addition, more specific buying recommendations could be put forward for each issue or challenge to be probed further.